Convenient One-Pot Synthesis of Allylsilanes from Enolizable Ketones - Kwan, Man Lung D.; Challen, Paul R.; Tran, Quynh D.-D. (SynOpen, 2019)
A convenient one-pot synthesis of allylsilanes from enolizable methyl aryl ketones has been developed. The first step involves nucleophilic addition of the trimethylsilylmethyl group to ketones using the alkylation method developed by Ishihara with slight modification to generate the corresponding β-silylalkoxides. The second step entails addition of diisobutylaluminum chloride and heating at about 130 °C overnight to afford allylsilanes in fair yields.
Keywords: abnormal Peterson olefination; allylsilane; one-pot synthesis